Pelatihan Soft Skill Karyawan Dalam Manajemen Bisnis Di Bali Beach Glamping - I Gede Dirga Surya Arya Widhyadanta; Ni Luh Gde Sari Dewi Astuti; Putu Herny Susanti (CV. Multi Kreasi Media, 2025)
One of the trending travel preferences among the upper-class segment, both domestic and international tourists, is glamping. Bali Beach Glamping is one such glamping destination that has been operating in Bali since 2021 and recorded a consistently high occupancy rate throughout 2023. The purpose of the training is to improve interpersonal skills, leadership, communication, and adaptability required in the working environment of Bali Beach Glamping. Through employee training, it is expected that the skills needed to carry out job responsibilities will increase, while also providing employees with the opportunity to grow both personally and professionally. As employees enhance their skills and knowledge, they will be able to deliver more valuable and productive contributions to the company. Based on the questionnaires completed by employees before and after the training, it can be concluded that employees’ understanding of soft skills and business management concepts has significantly improved. Awareness and application of these principles can help individuals and organizations achieve long-term success.